The effectiveness of booster vaccination of inactivated COVID-19 vaccines against susceptibility, infectiousness, and transmission of omicron BA.2 variant: a retrospective cohort study in Shenzhen, China - Liao, Yuxue; Su, Jiao; Zhao, Jieru; Qin, Zhen; Zhang, Zhuo’Ao; Gao, Wei; Wan, Jia; Liao, Yi; Zou, Xuan; He, Xiaofeng (Frontiers in Immunology, 2024)
Little studies evaluated the effectiveness of booster vaccination of inactivated COVID-19 vaccines against being infected (susceptibility), infecting others (infectiousness), and spreading the disease from one to another (transmission). Therefore, we conducted a retrospective cohort study to evaluate the effectiveness of booster vaccination of inactivated COVID-19 vaccines against susceptibility, infectiousness, and transmission in Shenzhen during an Omicron BA.2 outbreak period from 1 February to 21 April 2022. The eligible individuals were classified as four sub-cohorts according to the inactivated COVID-19 vaccination status of both the close contacts and their index cases: group 2-2, fully vaccinated close contacts seeded by fully vaccinated index cases (reference group); group 2-3, booster-vaccinated close contacts seeded by fully vaccinated index cases; group 3-2, fully vaccinated close contacts seeded by booster-vaccinated index cases; and group 3-3, booster-vaccinated close contacts seeded by booster-vaccinated index cases. Univariate and multivariate logistic regression analyses were applied to estimate the effectiveness of booster vaccination. The sample sizes of groups 2-2, 2-3, 3-2, and 3-3 were 846, 1,115, 1,210, and 2,417, respectively. We found that booster vaccination had an effectiveness against infectiousness of 44.9% (95% CI: 19.7%, 62.2%) for the adults ≥ 18 years, 62.2% (95% CI: 32.0%, 78.9%) for the female close contacts, and 60.8% (95% CI: 38.5%, 75.1%) for the non-household close contacts. Moreover, booster vaccination had an effectiveness against transmission of 29.0% (95% CI: 3.2%, 47.9%) for the adults ≥ 18 years, 38.9% (95% CI: 3.3%, 61.3%) for the female close contacts, and 45.8% (95% CI: 22.1%, 62.3%) for the non-household close contacts. However, booster vaccination against susceptibility did not provide any protective effect. In summary, this study confirm that booster vaccination of the inactivated COVID-19 vaccines provides low level of protection and moderate level of protection against Omicron BA.2 transmission and infectiousness, respectively. However, booster vaccination does not provide any protection against Omicron BA.2 susceptibility.